ISLAM, EDUCATION, AND MIGRATION IN INDONESIA: Religiosity Left-Behind Muslim Migrant Workers’ Children in East Java - Ardiansyah, Mochammad Zaka; Basri, Basri (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2025)
This article examines the religiosity of left-behind children, who are students at Islamic educational institutions, due to their parents' migration. While several studies on Indonesian migrants primarily highlight their religious activities abroad, this study focuses on the religiosity of ‘left-behind’ children in Jember, East Java, to understand the impact of migration on the religiosity and education of children. Left-behind children refer to those whose parents migrate for work, education, or other reasons, leaving them behind in their home countries with relatives or guardians. Several studies suggest that this situation can have a significant impact on the psychological and developmental well-being of children. The data were collected using a qualitative research design, which included participatory observation in informal Islamic education institutions and in-depth interviews with several education facilitators for children under 18 years old. To understand the religious dynamics among these children, this research employs El-Menouar’s dimension of religiosity as an analytical framework. The results identify two main issues appeared within the fields of Islamic education and migration studies: the conditions of children’s religiosity in the context of parental separation and the absence of informal education within the family and the proposal of the concept of Religiosity Left-behind as a new category to understand the spiritual and religious challenges faced by children of migrant workers. This research emphasizes the urgency of strategic interventions from educational stakeholders, including higher religious education institutions and civil society organizations, to design a sustainable program for the development of religiosity aimed at enhancing the quality of Islam and spirituality among children in left-behind situations.